2020
DOI: 10.1128/mra.00974-20
|View full text |Cite
|
Sign up to set email alerts
|

Draft Genome Sequences of Two Virulent Streptococcus equi subsp. zooepidemicus Swine Isolates from Pennsylvania

Abstract: Draft genome sequences of two outbreak isolates of Streptococcus equi subsp. zooepidemicus from a Pennsylvania swine herd affected with high mortality and morbidity are reported here. The genome analysis revealed that the isolates are closely related to a virulent strain originally identified in China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Canada was the first to report a high mortality event in North American swine due to S. zooepidemicus in March 2019 ( 4 ). A half year later, three outbreak cases of S. zooepidemicus occurred in culled sows and feeder pigs in Ohio, Tennessee, and Pennsylvania, with mortalities of up to 50% ( 1 , 5 ). Whole-genome sequencing analysis revealed that the outbreak isolates from Ohio and Tennessee clustered together with the prototype strain ATCC 35246, which caused high mortality outbreaks in China in the 1970s ( 6 ).…”
Section: Observationmentioning
confidence: 99%
“…Canada was the first to report a high mortality event in North American swine due to S. zooepidemicus in March 2019 ( 4 ). A half year later, three outbreak cases of S. zooepidemicus occurred in culled sows and feeder pigs in Ohio, Tennessee, and Pennsylvania, with mortalities of up to 50% ( 1 , 5 ). Whole-genome sequencing analysis revealed that the outbreak isolates from Ohio and Tennessee clustered together with the prototype strain ATCC 35246, which caused high mortality outbreaks in China in the 1970s ( 6 ).…”
Section: Observationmentioning
confidence: 99%